Integrating Aspect-Based Sentiment Analysis with CSI–IPA for Telecommunications App Development - Marshella, Siti Hariza; Kurniawan, Dedy; Oktadini, Nabila Rizky; Sanjaya, Rudi; Sevtiyuni, Putri Eka; Gumay, Naretha Kawadha Pasemah (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study integrates Aspect-Based Sentiment Analysis with Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) to determine priority development features in digital service applications in the telecommunications sector. A total of 10,000 MyIM3 user reviews were analyzed using sentiment analysis with Pseudo-labeling and Fine-Tuned IndoBERT, then from the results of the analysis, negative sentiment was mapped into several topics using LDA. The topic is used to compile question indicators based on the five dimensions of SERVQUAL. After the questionnaire data is declared valid and reliable, CSI and IPA analysis is carried out. A CSI value of 79.22% indicates that user satisfaction is in the